2015
DOI: 10.1186/s12977-015-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

South African HIV-1 subtype C transmitted variants with a specific V2 motif show higher dependence on α4β7 for replication

Abstract: BackgroundThe integrin α4β7 mediates the trafficking of immune cells to the gut associated lymphoid tissue (GALT) and is an attachment factor for the HIV gp120 envelope glycoprotein. We developed a viral replication inhibition assay to more clearly evaluate the role of α4β7 in HIV infection and the contribution of viral and host factors.ResultsReplication of 60 HIV-1 subtype C viruses collected over time from 11 individuals in the CAPRISA cohort were partially inhibited by antibodies targeting α4β7. However, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…Binding of the gp120 to the α4β7 integrin is not an essential requirement as is the binding to CD4 receptor or the CCR5 co-receptor but it is thought to be important only in the early stages of HIV-1 infection [171]. In fact, is has recently been shown in an acute infection cohort that the interaction with α4β7 varied between isolates and within individuals over time [177]. Nevertheless, HIV-1 target cells with high concentration of α4β7 has been shown to be more susceptible to HIV-1 infection, a factor that may also be attributable to the high levels of CCR5 found in these cells as well [178].…”
Section: Traits Reported To Be Different Between Transmitted/founder mentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the gp120 to the α4β7 integrin is not an essential requirement as is the binding to CD4 receptor or the CCR5 co-receptor but it is thought to be important only in the early stages of HIV-1 infection [171]. In fact, is has recently been shown in an acute infection cohort that the interaction with α4β7 varied between isolates and within individuals over time [177]. Nevertheless, HIV-1 target cells with high concentration of α4β7 has been shown to be more susceptible to HIV-1 infection, a factor that may also be attributable to the high levels of CCR5 found in these cells as well [178].…”
Section: Traits Reported To Be Different Between Transmitted/founder mentioning
confidence: 99%
“…A recent study has shown that challenging macaques intravenously with anti α4β7 antibodies protects them from a repeated dose challenge with SIV mac251 infection due to their GALT being protected from infection [179181]. In sum, α4β7 is used as an attachment factor that lowers the entropic barrier for binding of HIV-1 to CD4 and CCR5 which overall gives a selective advantage to the virus during the early stages of infection [177]. Some in vitro studies have failed to confirm the contribution of this integrin in HIV-1 infection [98, 163, 182, 183].…”
Section: Traits Reported To Be Different Between Transmitted/founder mentioning
confidence: 99%
“…However, our findings raise the possibility that there exists a link between the gut-tropic aspect of HIV infection and this physical interaction. It is possible that α 4 β 7 functions simply as an attachment factor [ 18 ]. However, gp120 binding to α 4 β 7 , like mucosal addressin cellular adhesion molecule (MAdCAM) transduces signals to primary CD4 + T cells, suggesting that such signals may be relevant to infection in vivo [ 9 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of prior studies have identified distinctive properties of TF variants [ 4 , 7 19 ], particularly in analyses of the TF viral envelope (Env) glycoprotein. Reported characteristics of TF virus Envs include a selection for CCR5-tropism [ 2 , 20 ], a predominance of shorter and less glycosylated Env proteins [ 1 , 11 , 15 , 18 , 19 ], a preference for binding α4β7 [ 10 , 21 ] and a selection for more ancestral variants [ 8 , 22 ]. Although these studies observed selection of viral traits, others found that acute and chronic variants had similar characteristics.…”
Section: Introductionmentioning
confidence: 99%